2018
DOI: 10.1038/s41386-018-0086-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the subjective and motivational properties of alcohol across alcohol use severity: application of a novel translational human laboratory paradigm

Abstract: The Allostatic Model proposes that Alcohol Use Disorder (AUD) is associated with a transition in the motivational structure of alcohol drinking: from positive reinforcement in early-stage drinking to negative reinforcement in late-stage dependence. However, direct empirical support for this preclinical model from human experiments is limited. This study tests predictions derived from the Allostatic Model in humans. Specifically, this study tested whether alcohol use severity (1) independently predicts subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 54 publications
4
32
1
Order By: Relevance
“…These results are also consistent with our recent work demonstrating that craving consistently predicted subsequent self-administration in the laboratory, even in the context of a progressive ratio translational task (Bujarski et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are also consistent with our recent work demonstrating that craving consistently predicted subsequent self-administration in the laboratory, even in the context of a progressive ratio translational task (Bujarski et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The first pathway suggests lower levels of response to the sedative and unpleasant effects of alcohol, and the second suggests higher sensitivity to the stimulant and pleasurable effects of alcohol (King et al, 2011, Schuckit, 1994, Schuckit and Smith, 1996. A recent study by our laboratory found that craving for alcohol during alcohol administration was a robust predictor of subsequent self-administration, such that greater self-reported craving was associated with higher levels of self-administration (Bujarski et al, 2018). In the same study we found that alcohol-induced sedation was associated with lower levels of selfadministration (Bujarski et al, 2018), which is consistent with longitudinal findings indicating that sedation may be protective against the development of an alcohol use disorder (AUD) (King et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature associating intravenous alcohol self‐administration paradigms with behavioral and clinical phenotypes is emerging. Intravenous alcohol self‐administration has been associated with family history of alcoholism (Zimmermann et al, 2009), drinking history (Bujarski et al, 2018; Stangl et al, 2017), including binge drinking (Sloan et al, 2019), AUD risk (Gowin et al, 2017), craving (Green et al, 2019; Wardell et al, 2015), personality traits (Stangl et al, 2017; VanderVeen et al, 2016), sex differences (Cyders et al, 2016; Plawecki et al, 2018b), pharmacologic targets or interventions (Suchankova et al, 2017), and risk genotypes (Hendershot et al, 2016, 2017; Plawecki et al, 2013; Sloan et al, 2018; Suchankova et al, 2017).…”
Section: Issues To Consider In Choosing Route Of Administrationmentioning
confidence: 99%
“…In light of the emerging role of functional neuroimaging in predicting drinking behavior and AUD treatment outcomes, a remaining question is the nature of the relationship between neuroimaging task‐induced neural activation and widely utilized laboratory paradigms considered proximal to real‐world consumption, including self‐administration tasks. To date, several studies have examined relationships of response across different laboratory paradigms (i.e., subjective response and self‐administration) and have consistently identified that alcohol craving during intravenous alcohol administration mediates the relationship between alcohol‐induced stimulatory effects and subsequent oral alcohol consumption (Bujarski et al, 2018; Green et al, 2019; Wardell et al, 2015). While relationships across human laboratory paradigms are recently delineated, no studies have yet investigated whether alcohol cue–induced BOLD response is predictive of responses within laboratory self‐administration paradigms.…”
mentioning
confidence: 99%